Successful Use of Pulmonary Vasodilators in Acute Chest Syndrome Complicated by Persistent Right Ventricular Failure - Jacqueline T. DesJardin; Lucas S. Zier (Case Reports in Cardiology)
Pulmonary hypertension (PH) is a known consequence of sickle cell disease (SCD) and is associated with increased mortality and more frequent episodes of acute chest syndrome (ACS). Pulmonary pressures are known to increase during ACS, and right ventricular (RV) failure has been described as a significant cause of mortality in this condition. Management of ACS includes exchange transfusion, pain control, and prevention of hypovolemia and hypoxemia. However, in patients with a history of precapillary PH in whom ACS is complicated by persistent RV failure and cardiogenic shock, RV afterload reduction with pulmonary vasodilators may be an effective treatment strategy. Here, we present a case of a young man with SCD-associated PH and ACS who was successfully managed with inhaled and oral pulmonary vasodilators in the setting of persistent elevations in pulmonary vascular resistance leading to acute RV failure and cardiogenic shock.